Retrospective Evaluation of Patients Presenting to the Pediatric Emergency Department with Syncope - Yildiz, Mustafa; Kirik, Serkan; Gökdere, Gökhan (Ortadogu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2026)
Objective: To compare the demographic characteristics and laboratory parameters of children presenting with syncope to the emergency department of a tertiary pediatric hospital in Turkey with those of healthy children evaluated during routine visits, and to assess the diagnostic contribution of commonly ordered laboratory tests to help reduce unnecessary testing. Material and Methods: This retrospective study, conducted between November 2024 and February 2025 at a tertiary center, included 352 patients aged 2–17 years and 489 healthy controls. Exclusion criteria were acute infection, moderate–severe dehydration, use of antiarrhythmics, diuretics, or steroids, known heart disease, channelopathy, epilepsy, or chronic kidney or liver disease. Laboratory samples were obtained within the first 60 minutes. Statistical analyses were performed using appropriate methods, with significance set at p<0.05. Results: Compared with controls, the syncope group had significantly higher white blood cell, neutrophil, monocyte, glucose, and urea levels, and significantly lower lymphocyte and eosinophil percentages, plateletcrit, platelet, sodium, and potassium levels; hemoglobin was similar. In age-stratified analyses, children aged 2–7 years showed hematologic increases accompanied by higher glucose and lower sodium levels, while several biochemical parameters varied by age. These findings suggest a more pronounced physiological stress response in younger children. Conclusion: Certain laboratory alterations in pediatric syncope may reflect acute stress and autonomic responses. History, physical examination, and electrocardiography remain fundamental, while targeted laboratory testing may provide additional value. Considering age-related physiological differences may help reduce unnecessary testing; prospective studies are needed to clarify their role in risk stratification. Copyright © 2026 by Türkiye Klinikleri.
Çocuk Acil Servisine Senkop Nedeniyle Başvuran Hastaların Retrospektif Değerlendirilmesi
Keywords: adolescent; pediatric emergency medicine; pediatrics; psychological stress; Syncope